Design and application of a nursing pad for prevention of pressure injuries (一种防压疮护理垫的设计与应用) - LIU Jiao (刘娇); LIU Lu (刘璐); SUN Xiumei (孙秀梅) (中西医结合护理)
Pressure injury is one of the most common complications in long-time bedridden patients, and it is an important sensitive index of clinical nursing quality. This study introduces the design and use method of a utility model nursing pad for prevention of pressure injuries, which can increase the comfort and breathability of patients, reduce the work burden of medical staff and improve work efficiency. (压力性损伤是临床长期卧床患者最常见的并发症之一, 压力性损伤的发生率是临床护理质量的重要敏感指标。本研究介绍了一款实用新型防压疮护理垫的设计和使用方法, 具有良好的舒适和透气性, 护理垫便于换洗, 且能够辅助患者进行翻身, 有助于提高护理人员工作效率。)